2003
DOI: 10.1063/1.1537872
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous hard x-ray emission mode in a plasma focus discharge with hydrogen-argon mixtures

Abstract: We observed an anomalous discharge mode causing explosive surface evaporation and emission of hard x rays of 10–40 keV in the regime of the lower hydrogen partial pressures of hydrogen–argon mixture in a Mather type plasma focus device of 1.5 kJ. At the anomalous mode, the x rays were emitted from only the surface of the anode without emissions from a plasma column or hot spots, accompanying with explosive evaporations of the anode surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The HXR pulses produced by the interaction of localized electron beams at the anode tip of the device are excel lent candidates for radiography of dynamic biological specimens and metal objects [9]. Anomalous HXR emission mode was investigated by Heo et al [10]. Time resolved measurements showed that the power law spectrum (dN HXR /dE ~E -a , where а is in the range of 2 to 4, Е is in keV, and N HXR is the HXR flux in pho tons/cm 2 ) found for the plasma focus in the range of 100 to 500 keV is the result of time integration over…”
Section: Introductionmentioning
confidence: 99%
“…The HXR pulses produced by the interaction of localized electron beams at the anode tip of the device are excel lent candidates for radiography of dynamic biological specimens and metal objects [9]. Anomalous HXR emission mode was investigated by Heo et al [10]. Time resolved measurements showed that the power law spectrum (dN HXR /dE ~E -a , where а is in the range of 2 to 4, Е is in keV, and N HXR is the HXR flux in pho tons/cm 2 ) found for the plasma focus in the range of 100 to 500 keV is the result of time integration over…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Due to its simplicity, versatility, compactness, cost-effectiveness, and easy maintenance, PF is particularly attractive for both basic and applied research. An important part of the recent experimental studies on x-ray and particle emission from PF is oriented in interesting applications such as contact microscopy, x-ray and electron beam lithography, generation of soft x-ray spectral lines of highly charged heavy metal ions, metal coating by ion sputtering, surface modification and deposition of thin films, x-ray backlighting, radiography of biological and mechanical objects, and micromachining.…”
Section: Introductionmentioning
confidence: 99%